EXAMINING THE ROLE AND SIGNIFICANCE OF EMERGING SOCIAL NEWS OUTLETS AND THEIR ADVOCACY JOURNALISM IN THE 2017 AUSTRALIAN SAME-SEX MARRIAGE POSTAL SURVEY - Hurcombe, Edward Flipo (AoIR Selected Papers of Internet Research, 2018)
This paper examines emerging news forms and journalistic practices within Australia that are native to social media. It argues that these shared forms and practices constitute a new genre of ‘social news’. Social news embodies specific kinds of platform vernaculars and pop-cultural sensibilities, and challenges journalistic norms of ‘objectivity’ and ‘balance’ by consistently adopting an overtly positioned perspective. Three Australian-based outlets are studied through this conceptual lens: BuzzFeedOz News, Junkee Media, and Pedestrian.tv. Using digital tools alongside manual methods, this paper investigates the role and significance of these outlets on Twitter and Facebook during the August-November 2017 same-sex marriage postal survey. The survey was commissioned by the incumbent conservative Liberal-National Australian government to gauge nationwide support for same-sex marriage. During the survey, social news outlets played an advocacy and activist role. These outlets refrained from publishing provocative ‘No’ op-eds, and Junkee Media and Pedestrian.tv actively encouraged readers to enrol and vote ‘Yes’. Preliminary findings indicate that social news outlets were moderately-to-highly visible on Twitter during the postal survey period. On Facebook, advocacy posts received low-to-moderate levels of engagement. These findings indicate a shifting but not yet transformed Australian news ecology. In addition, social news’ eschewing of ‘balance’ indicates a challenge from emerging outlets to traditional journalistic norms in Australia. Significantly, in this case the challenge comes from outlets that intelligently critique the value in publishing both sides. Overall, this research highlights that disruptions from social media platforms and cultures can be sources of positive potential for news and journalistic practice.